Improvement of Effectiveness by Applying PDCA Cycle or Kaizen: An Experimental Study on Engineering Students (Journal of Scientific Research, 2018)
This study mainly focused on developing skills on different field of perspective like software-based skills and interpersonal skills which will help an individual to become more proactive and efficient in their desired job field. In this memorizing based educational system students are not encouraged to learn new skills like software-based skills and interpersonal skills which are very much important to become expert and qualified individual in the corporate and competitive job field. The aim was to develop an effective method which will help the students to learn these necessary skills besides their regular course related study. It was focused on using this method by approaching on a gradual step by step procedure and developed it to solve the problem. It will save the time of the students and also make their fundamental knowledge strong on different software. A survey was conducted among the students from own university and got a satisfactory response from them. Most of them were looking for an effective process of learning without harming regular studies. This method will obviously help the students of our country to improve skills besides regular studies in a more effective way to be expert in their own field of specialization.